The Influence of MoOx Anode Stoicheometry on the Performance of Bulk Heterojunction Polymer Solar Cells. Issue 7 (5th April 2013) - Griffin, Jonathan; Watters, Darren C.; Yi, Hunan; Iraqi, Ahmed; Lidzey, David; Buckley, Alastair R.
Abstract Bulk heterojunction solar cells containing molybdenum oxide hole extracting anode contacts have been fabricated with varying stoicheometry using radio frequency reactive sputtering from a Molybdenum metal target. A blend of the newly synthesised conjugated polymer poly[9‐(heptadecan‐9‐yl)‐9H‐carbazole‐2, 7‐diyl‐alt‐(5, 6‐bis(octyloxy)‐4, 7‐di(thiophen‐2‐yl)benzo[c][1, 2, 5]thiadiazole)‐5, 5‐diyl] (PCDTBT‐8) and fullerene [6, 6]‐Phenyl‐C71‐butyric acid methyl ester (PC70BM) was used as the photoactive layer and device results show that anodes with greater than 98% Molybdenum (VI) oxide result in peak power conversion efficiencies of 3.7%.The presence of up to 28% of Mo (V) results in no significant reduction in efficiency, however the presence of metallic Mo (IV) and lower oxidation states lead to severe reductions in device performance due to a combination of a large hole extraction energy barrier of approximately 0.9eV and reduced device stability.